Histopathological audit of splenectomies received at a cancer hospital - Sumeet Gujral; Poornima Lad; P G Subramanian; T M Shet; S Epari; S Laskar; M Muckaden; H Menon; M Sengar; R Nair (Wolters Kluwer Medknow Publications, 2011)
Background: There are few studies in the literature studying the yield of the diagnostic splenectomy in a suspicious lymphoma case. Moreover, their relevance is limited owing to low number of cases, the use of selection criteria, and the lack of modern ancillary studies. We present a histopathological review of splenectomy specimens referred as a case of lymphoma to our center. Materials and Methods: The medical charts and laboratory data on all patients of all splenectomy specimens between the years 2003 and 2008 were reviewed. Morphological and immunohistochemical features were analyzed and the lymphomas were sub-typed in accordance to 2008 WHO Classification of Hematolymphoid Neoplasms. Flow cytometry immunophenotyping available in few cases was correlated. Results: A total of 46 cases studied included splenic marginal zone lymphoma (SMZL) (19 cases), splenic diffuse large B-cell lymphoma (DLBCL) (14 cases), splenic diffuse red pulp B-cell lymphoma (DRP) (five cases), follicular lymphoma (three cases), hairy cell leukemia (HCL) (two cases), HCL variant (HCLv) (1 case), 1 case of hepatosplenic gamma delta T-cell lymphoma (TCL), and 1 cases of TCL (not otherwise specified). Conclusions: Predominantly splenic lymphoma is a biologically heterogeneous entity, ranging from low-grade SMZL to high-grade DLBCLs. TCLs constituted only 4% of all our cases. DRP, HCL, and HCLv have similar diffuse red pulp patterns of splenic involvement and are differentiated based on flow cytometric immunophenotyping. We had a large number of splenic DLBCL and none of these involved bone marrow (BM), while all other lymphoma subtypes had BM involvement (stage IV disease). Morphological and immunophenotypic (immunohistochemistry and flow cytometry) features of BM and splenectomy specimen need to be correlated to differentiate these rare though similar-looking entities with overlapping features.